The Role of Digital Leadership in Improving MSME Performance: Perspective of Information and Communication Technology (ICT) Utilization - Andi Batary Citta; Ahmad Ridha. T (www.amertainstitute.com, 2024)
This study explores the role of digital leadership in improving the performance of Micro, Small, and Medium Enterprises (MSMEs) through the use of Information and Communication Technology (ICT). Using a qualitative approach, data were collected through literature review, in-depth interviews with MSME leaders and field observations. The results showed that MSME leaders utilize Information and Communication Technology (ICT) to improve efficiency and competitiveness, despite challenges such as limited resources and resistance to change. Successful strategies include gradual technology adoption, employee training, and external collaboration. In addition, participatory and transformational leadership have proven effective in creating a culture of innovation that supports the digitalization process. This study provides theoretical and practical contributions by highlighting the importance of Information and Communication Technology (ICT), which is a strategic resource in accelerating the digital transformation of MSMEs.